Demotivation Factors of English Language Preservice Teachers: A Mixed-Method Study - Adara, Reza Anggriyashati; Hamer, Weliam; Nur Lely, Ledy; Rohimajaya, Nur Azmi (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
Understanding the factors that demotivate English language pre-service teachers is crucial, as these future educators will significantly influence their students’ motivation and engagement with language learning. This study investigates key demotivation factors among pre-service teachers enrolled in an English education program at a public university in Indonesia. Using a sequential explanatory design, data were collected through questionnaires distributed to pre-service teachers, followed by semi-structured interviews with four selected participants. Quantitative data were analyzed using SPSS 23, while qualitative data were examined through thematic analysis. The quantitative findings reveal that a lack of intrinsic motivation, along with concerns about teacher competence and teaching styles, are the most prominent demotivating factors. The qualitative findings further reveal that performance pressures such as test scores intensify these experiences, helping to explain how certain factors become highly demotivating despite their lower statistical prominence. The study also contributes theoretically by extending Sakai and Kikuchi’s demotivation framework, showing how teacher-related issues, learning content, and learner psychology interact to shape pre-service teachers’ demotivation in the Indonesian EFL context. This can be achieved through more engaging coursework, opportunities for meaningful teaching experiences, and mentorship by competent educators. Furthermore, ongoing professional development for in-service teachers should also prioritize strategies to maintain motivation and improve instructional quality. By addressing these factors, both pre-service and in-service teachers will be better equipped to create motivating classroom environments, ultimately enhancing students ’ learning of English as a foreign language. The implications of these findings underscore the urgent need for teacher education programs to focus on developing and sustaining pre-service teachers’ intrinsic motivation.